Peran Amal Usaha Muhammadiyah Bidang Pendidikan Dalam Pendidikan Nasional - Imam Ma’arif; Muh. Akbar (STIKes Ibnu Sina Ajibarang, 2024)
Since its founding by KH. Ahmad Dahlan to the present day, Muhammadiyah has played a central role in developing educational concepts, overcoming various historical challenges such as illiteracy and the colonial era, and continuously improving education standards while empowering communities. This research aims to describe Muhammadiyah's Educational Philosophy, Muhammadiyah's Educational History, Muhammadiyah's Struggle and Efforts in the Field of Education, as well as Muhammadiyah's Contribution to National Education. Through a literature review method, this study reveals how Muhammadiyah, as the largest Islamic organization in Indonesia, undertakes tajdid and ijtihad in developing education based on Islamic teachings to achieve the goal of creating an Islamic society in line with religious values. Muhammadiyah's educational philosophy emphasizes the harmony between religious and general knowledge, integrating various aspects of life. As a pioneer of Islamic educational reform, Muhammadiyah also plays a strategic role in raising national awareness and spreading modern knowledge in society, building a just, empowered, and morally upright community in accordance with Islamic teachings.